2022
DOI: 10.18662/po/13.2/441
|View full text |Cite
|
Sign up to set email alerts
|

Training Technologies as a Means of Communicative Competences Development of Prejudicial Inquiry Agencies’ Investigators

Abstract: The communicative component of the investigator’s professional activities is a dominant one, as it demonstrates the employee’s ability to organize work on the basis of professionally balanced communication with the objects of interaction. The stage of obtaining higher education in institutions with specific learning environment is a sensitive period for the development of the main sociogenic structures of personality and the development of professional identity of future professionals. This period is character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The publications analysed by us (Miloradova, Okhrimenko, Dotsenko, Matiienko, & Rivchachenko, 2022;Zahorodna, Saienko, Tolchieva, Tymoshchuk, Kulinich, & Shvets, 2022) indicate that there is no single definition of the concept of communicative competence in the scientific literature. Taking into account the interpretation of the concepts of competency and competence in regulatory documents, we understand the communicative competence of an individual as the socially recognized level of certain communicative knowledge, abilities and skills, value attitudes towards the communication process.…”
Section: Discussionmentioning
confidence: 99%
“…The publications analysed by us (Miloradova, Okhrimenko, Dotsenko, Matiienko, & Rivchachenko, 2022;Zahorodna, Saienko, Tolchieva, Tymoshchuk, Kulinich, & Shvets, 2022) indicate that there is no single definition of the concept of communicative competence in the scientific literature. Taking into account the interpretation of the concepts of competency and competence in regulatory documents, we understand the communicative competence of an individual as the socially recognized level of certain communicative knowledge, abilities and skills, value attitudes towards the communication process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our research confirmed our earlier opinion that successful police officers are characterized by controlled behavior, selfcontrol, perseverance, diligence, thoroughness, responsibility, discipline, a low level of neuroticism, the absence of depressive and hypochondriac tendencies, etc. (Aleksandrov et al, 2017;Bondarenko et al, 2021;Miloradova et al, 2022;Ponomarenko et al, 2022).…”
Section: Limits and Discussionmentioning
confidence: 99%
“…Результативність проведення більшості слідчих (розшукових) дій (допит, одночасний допит двох раніше допитаних осіб, слідчий експеримент та ін.) в багатьох випадках залежить від розуміння слідчим психологічних особливостей професійного спілкування [8]. Тому доцільним є приділення належної уваги при підготовці фахівців розвитку саме комунікативної складової професійної діяльності.…”
Section: Goetheunclassified